2016
DOI: 10.1016/j.jfma.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 4-γ, 1 gene mutations are rare in Parkinson's disease among Taiwanese

Abstract: This study indicates that the EIF4G1 mutation is rare in Taiwan, which is consistent with other reports from Asia. Ethnicity could have a great influence on EIF4G1 in PD. Further large scale studies are warranted to evaluate the association of PD and EIF4G1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, surgery, rehabilitation and palliative care are used for Parkinson's disease treatment as well [125]. The causes of Parkinson's disease are attributed to age, low serum urate concentrations, smoking, α-synuclein mutations, leucine-rich repeat kinase 2, phosphatase, tension homolog-induced putative kinase 1, parkin 7, vacuolar protein sorting 35, receptor-mediated endocytosis 8 as well as coiled-coil-helix-coiled-coiled-helix domain containing 2 [124] and eukaryotic translation initiation factor 4-γ [126]. In addition, leucine-rich repeat kinase 2 mutations also exacerbate disease progression by activating the Wnt/β-catenin pathway in adult mice and cultured fibroblasts [127].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, surgery, rehabilitation and palliative care are used for Parkinson's disease treatment as well [125]. The causes of Parkinson's disease are attributed to age, low serum urate concentrations, smoking, α-synuclein mutations, leucine-rich repeat kinase 2, phosphatase, tension homolog-induced putative kinase 1, parkin 7, vacuolar protein sorting 35, receptor-mediated endocytosis 8 as well as coiled-coil-helix-coiled-coiled-helix domain containing 2 [124] and eukaryotic translation initiation factor 4-γ [126]. In addition, leucine-rich repeat kinase 2 mutations also exacerbate disease progression by activating the Wnt/β-catenin pathway in adult mice and cultured fibroblasts [127].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Subsequently evidence has suggested that R1205H is only a benign polymorphism (Dhungel et al, 2015 ) as a number of studies identified R1205H in both patients and controls (Nuytemans et al, 2013 ; Dhungel et al, 2015 ; Nichols et al, 2015 ). The majority of South African and Asian studies (Quadri et al, 2013 ; Nishioka et al, 2014 ; Weng et al, 2015 ) failed to identify EIF4G1 mutations either in patients or in controls (Sudhaman et al, 2013 ). In Caucasians the mutations occur in 11.57% familial cases and 0.09% sporadic cases (Sudhaman et al, 2013 ).…”
mentioning
confidence: 99%
“…Modulation of retromer function by increasing the level of VPS35 could enhance intracellular transport. It was shown in pre-clinical studies that the enhancement of the retromer function reverses the neurotoxic effects without any obvious toxicity, however further studies are needed (Weng et al, 2015 ).…”
mentioning
confidence: 99%